PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR SISWA KELAS VIII MTs SEJAHTERA BERSAMA RAMBAH SAMO - Efriani, Elda; Afri, Lusi Eka; -, Arcat (Universitas Pasir Pengaraian, 2015)
This purpose of this research is what arc the effect learning problem posing model in learning process mathematicat the score of second year of MTs Sejahtera Bersama Rambah Samo. Based on the result analisis Statistic usednon parametrik that is mann whitney test. The score of this results is 51 and than U table is 5% should besignificant 69. So U < U table. This showed the alternative hypothesis (H1) is not significant and hypothesis nol(H0) is significant. So, there is effect of learning problem posing to the result of the second year student of MTsSejahtera Bersama Rambah Samo.